Gender Budgeting in Kerala: An Analysis towards Women’s Health - A Jayasree (RESEARCH ESSENCE, 2013)
The paper attempts to study the share of budgetary resources allotted to women’s health in budgets of Kerala in relation to Government policy declaration during the period 2003-04 to 2009-10. The overall objective is to evaluate the gender sensitiveness of the budget in terms of provisions for women’s health. Even though a fairly satisfactory allocation is made towards women’s health in terms of total outlay the actual expenditure on women specific schemes (WSS) is only a considerably lower fraction of it. In terms of total plan expenditure, the commitments were fulfilled at a higher level. The gender budgeting exercise also demonstrates that only a small portion of the non-plan expenditure is specifically allocated towards women's health and the allotment towards it has not been consistent with time and inadequate in most of the years